CARING THE ELDERLY IN BASIC HEALTH UNIT (Fiep Bulletin - online, 2013)
The units of family health are the main responsibility for care for the elderly, since a good part of this population is unable to enjoy a private system, which is important for people with low income and living in precarious conditions of housing. This is a documentary study from data obtained in the Information System of Primary Care (ISPC) of DATASUS, from 2004 to 2006, provided by the Municipal Health Secretariat of the city of Joao Pessoa, Paraiba, Brazil. According to the data realizes that there was an increase in the number of elderly in Joao Pessoa, registered in the Unit, the coverage of care to the elderly population is concentrated in densely populated neighborhoods. The data suggest the main cause of deaths with cardiovascular disease note that there was a growth in population over 60 years in the city of Legaspi, reflecting, therefore, by increasing the number of elderly people registered in basic health units and the coverage of them. Over the years the health teams have been remedial, able to ensure that the elderly are aware of the importance of the drive to register and take part in groups for each age group. The elderly are covered with "HiperDia" with care toward them and to their needs, although the population will always drive, and the most visited at the home visits.
Keywords: Primary Care; Elderly; Nursing